SUCCESSFUL HR AUDIT: IS IT DETERMINED BY TOP MANAGEMENT COMMITMENT, HR CONSULTANTS, AND LINE MANAGER INVOLVEMENT - Fredson Kotamena; Poltak Sinaga; Dylmoon Hidayat; Niko Sudibjo (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2022)
The research aimed to find out how to execute a successful HR audit by looking into the top management's commitment, HR consultants' function in the business, and the line manager's level of participation in the audit. 70% of the total population of employees who were selected using probability random sampling participated through an online questionnaire. The hypothesis was tested using structural equation modeling since a total of 104 respondents supplied favorable responses, but only 101 could be employed to test the hypothesis. The result showed that the absence of HR and line managers did not affect the success of HR audits from the starting point and that the term